Kātibî ve Gencine-i Adaleti - Karpuz, Hacı Ömer; Aydemir, Özgür Kasım (My University, 2011)
7. yüzyılda yazılmış olan Gencine-i Adalet, Osmanlı Devleti Padişahı Sultan I. Ahmed’e sunulmuş telif bir siyasetnamedir. 17. yüzyılda talik hatla yazılmış olan Gencine-i Adalet 360 sayfadan oluşmaktadır. Eser, Topkapı Sarayı Müzesi I. Ahmed Yazma Eserler Müzesi’nde bulunmaktadır. Eser ve müellifinin özellikleri doğrulsunda ulaşılacak bilgiler, dilbilimin yanı sıra halk biliminin ve tarihin de ilgi alanına yönelik sonuçlara uç vermektedir. Çalışmada, hakkında sınırlı bilgilye ulaşılabilen ve tek nüsha olan siyasetname türündeki Gencine-i Adalet’e ve müellifi Katibi’ye ilişkin özelliklerin belirtilmesi amaçlanmıştır.

Gencine-i Adalet, written in the 17th century, is a compilation book of government which is presented to I. Ahmed, Sultan of the Ottoman Empire. Written with a talik lettering Gencine-i Adalet consists of 360 pages. This work is now in Topkapı Palace museum, manuscripts museum of I. Ahmed. The informations which is reached in parallel with the work and its author’s characteristics point out the results in, besides linguistics, field of interests of folklore and history. This work aims to define the characterics of Gencine-i Adalet, the only book of government copy about whom a limited information is reached, and its author Katibi.
Katibi and Gencine-i Adalet’s
Keywords: El yazması; siyasetnâme; Gencine-i Adalet; Kâtibî; I. Ahmed; İktidar; Manuscript; Power